Fertilization and sustainable nutrition of oil palm (Elaeis guineensis) in Tabasco, Mexico - Salgado Garcia, Sergio; Palma Lopez, David Jesus; Zavala Cruz, Joel; Lagunes Espinoza, Luz del Carmen; Córdova-Sánchez, Samuel; Castelan Estrada, Mepivoseth; Ortiz Garcia, Carlos Fredy; Rincón Ramírez, Joaquin Alberto; Salgado Velazquez, Sergio (Ecosistemas y Recursos Agropecuarios, 2023)
The cultivation of oil palm in the state of Tabasco is the main producer. The objective of this work was to generate a fertilization dose per soil subunit and a potential yield for oil palm. The methodology of the Integrated System to Recommend Fertilizer Doses (SIRDF) was used. Eight Thiessen polygons were obtained, which were grouped into low (1 281 to 1 623 mm), medium (1 830 to 1 977 mm) and high precipitation (>2 044 mm) polygons. In addition to 13 soil subunits, of which only 11 are cultivated with oil palm: Leptosol Réndzico (Humic), Luvisol Gléyico (Arcíllico, Eutrico, Diferéntico), Acrisol Gléyico Crómico (Eutrico, Loamy, Cutánico, Diferéntico), Calcisol Pétrico Cambic (Franky, Ruptic), Gleyic Eutric (Franky) Cambisol, Phaeozem Réndzic Leptic Cambic (Arcyllic), Pelic Vertisol (Gleyic, Mesotrophic, Stagnin), Gleyic Calcaric (Arcyllic) Fluvisol, Oxygleyic Dystric (Arcyllic, Vertic) Gleysol, Abruptic Lixisol (Claylic, Cutanic), and Dystric Arenosol (Aluminic). Soil analysis indicates medium to low fertility with deficiencies of N, P, K, Ca, Fe, Zn, Cu, and B. The fertilizer dose was generated for each soil subunit and for three fresh fruit yield scenarios. Recommendations for macro and micronutrients were generated to achieve a balanced fertilization of the oil palm and its form of application.